Fasting and 24-h urine pH in patients with urolithiasis using potassium citrate - Silva, Isabela Bertanholi Leme da [UNESP]; Amarol, Carmen Petean [UNESP]; Amaro, Joao Luiz [UNESP]; Cunha, Natalia Baraldi [UNESP]; Callegari, Matheus Augusto [UNESP]; Yamamoto, Hamilto Akihissa [UNESP]; Guerra, Rodrigo [UNESP]; Quitzan, Juliany Gomes [UNESP]; Reis, Leonardo O.; Kawano, Paulo Roberto [UNESP] (E-century Publishing Corp, 2022)
Purpose: To evaluate the correlation between the pH readings in 24 h urine and the random fasting specimen in patients with urolithiasis using 2 methods. Methods: A total of 114 patients with urinary lithiasis using potassium citrate were prospectively analyzed. All patients collected 24-h urine and an additional sample, after nocturnal fasting, collected on the day they brought the 24-h sample at the lab. Two different methods (test strip and digital meter) were used to determine pH values. Results: The pH analysis using strips in the 24-h urine presented a mean value similar to the one obtained in the fasting sample (6.07 +/- 0.74 vs. 6.02 +/- 0.82, respectively; P > 0.05). The same behavior was seen considering the readings with a digital pH meter (5.8 +/- 0.78 vs. 5.75 +/- 0.83; P > 0.05). However, readings conducted in the same specimen with pH meter and test strip were dissonant (P < 0.05), suggesting that the colorimetric method is not reliable in the assessment of urinary pH in this population. Conclusion: pH assessment in a random urinary specimen proved as efficient as the 24-h urine standard method to monitor patients with kidney stones in the use of potassium citrate. Classical test strip analysis is not sensitive enough to evaluate the urine pH in this population and digital pH meter reading is preferred.
Keywords: 24-h urine; Nephrolithiasis; Potassium citrate; Urinary pH; Random urinary specimen